Re-Connecting Community Collective Memory with the Change of Life Culture and the Cultural Resistance in Paku Alam Village, Sumedang, West Java, Indonesia - Dhini Dewiyanti; Tri Widianti Natalia; Nova Chandra Aditya (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2021)
Development can be described as two sides of a coin, the first side provides benefits, but on the other side it turns out to have to sacrifice for some people. Jatigede Dam, located in Sumedang Regency, West Java Province, was built in 1998 and its construction resulted in 28 submerged villages. The communities whose areas are submerged must create new villages and switch professions that used to have a livelihood as an agrarian society must switch professions to become aquatic culture communities. This paper discusses experiences in the proposed (re)structuring activities of the Paku Alam Village area in Darmaraja District around the dam. The activity is carried out through the method of recalling the community collective memory, which is brought together with the context of changes in the livelihood culture and ritual culture that is still owned by the village community so that the changing area can be accepted as a